SUBJECTIVE WELL-BEING AS AN EFFICIENCY INDICATOR OF PUBLIC POLICY - GHARAGULYAN, ARMAN (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The pursuit of happiness is a human attributive feature. For centuries, philosophers have touched upon this topic, but there are relatively few works where happiness is seen as an object of public policy. In recent decades, the development of methods for measuring subjective well-being has evolved, thereby integrating new performative indicators into policies along with classic economic approaches. The article analyzes the conceptual apparatus of such studies, the relationship between “happiness” and “well-being” (economic and subjective), examples of theoretical and successful political initiatives, and further prospects for such studies.